Pengaruh Penambahan Vitamin B pada Media Blotong 12 Kering terhadap Pertumbuhan Populasi Dunaliella salina [Effect of Adding Vitamin B on Blotong Dry Media 12 Againts Population Growth Dunaliella salina] - Rahayu Kusdarwati; Mustofin Akhyar; Boedi S. Rahardja (Jurnal Ilmiah Perikanan dan Kelautan, 2011)
Abstract Dunaliella salina is one natural food that is good enough for the larvae of sea urchins and also can be used as food Brachionus plicatilis and Artemia in aquaculture feed Artemia. Blotong is precipitated in the process of purification juice before cooking and crystallized into sugar. Purification is a process to separate the juice from dirt or fibers. Sugarcane is used as fertilizer by using oven dried first. Vitamin B is needed some algae to build 12 proteins and essential as a coenzyme necessary for DNA synthesis in the formation of new cells. Vitamin B is a 12 coenzyme B -dependent methionine synthase and vitamin B -dependent ribonucleotide reductase. Vitamin B 12 12 12 dependent methionine synthase function for synthesis methionin (essential amino acids), whereas vitamin B 12 dependent ribonucleotide reductase functions to DNA synthesis. This study aims to determine the effect of vitamin B in dry blotong media on the growth of D. salina 12 population and to determine the optimal dosage of vitamin B in dry blotong media which can produce the highest 12 population growth of D. salina. This research used Completely Randomized Design (CRD) with seven treatments and three replications. The study used namely: Fertilizer blotong dried with the addition of vitamin B 10 g / L (A), dose of 12 12 ug / L (B), the dose of 14 ug / L (C), a dose of 16 ug / L (D), dose 18 ug / L (E), a dose of 20 ug / L (F) and control treatment of dry sugarcane fertilizer without adding vitamin B12 or dose 0 g / L (G). The main parameter used is the population of D. salina, while supporting the water quality parameters (salinity, pH and water temperature). Data were analyzed with ANOVA (analysis of variants) and to know the differences among the treatments performed Duncan's Multiple Range Test. The results showed that the addition of vitamin B in dry blotong media had no effect on the growth of population D. salina (p> 0.05).